2021
DOI: 10.3390/jcm10153407
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Central Compartment Involvement in Patients with Positive Lateral Cervical Lymph Nodes According to Clinical and/or Ultrasound Evaluation

Abstract: Lymph node neck metastases are frequent in papillary thyroid carcinoma (PTC). Current guidelines state, on a weak level of evidence, that level VI dissection is mandatory in the presence of latero-cervical metastases. The aim of our study is to evaluate predictive factors for the absence of level VI involvement despite the presence of metastases to the lateral cervical stations in PTC. Eighty-eight patients operated for PTC with level II–V metastases were retrospectively enrolled in the study. Demographics, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…In this scenario, unilateral PTC patients with highly suspected or intraoperative pathological diagnosed skip metastasis may benefit more from thyroid lobectomy (TL) with therapeutic compartmental lateral neck dissection instead of total thyroidectomy (TT) 33,34 . Recent research showed that N1b patients with no evidence of CLNM might not require or benefit from prophylactic CND, which provided patients with skip metastasis a possibility of less aggressive treatment strategy 35,36 . In terms of adjunctive treatment, routine RAI and moderate or complete TSH‐suppressive therapy may not be necessary as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, unilateral PTC patients with highly suspected or intraoperative pathological diagnosed skip metastasis may benefit more from thyroid lobectomy (TL) with therapeutic compartmental lateral neck dissection instead of total thyroidectomy (TT) 33,34 . Recent research showed that N1b patients with no evidence of CLNM might not require or benefit from prophylactic CND, which provided patients with skip metastasis a possibility of less aggressive treatment strategy 35,36 . In terms of adjunctive treatment, routine RAI and moderate or complete TSH‐suppressive therapy may not be necessary as well.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 Recent research showed that N1b patients with no evidence of CLNM might not require or benefit from prophylactic CND, which provided patients with skip metastasis a possibility of less aggressive treatment strategy. 35 , 36 In terms of adjunctive treatment, routine RAI and moderate or complete TSH‐suppressive therapy may not be necessary as well. Although the population of skip metastasis patients is not large, huge improvements in physiological, psychological, and social benefits are worthy.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that micro pT3 makes up 25% of all pT3, and up 15% of all PTmC. In the light of current knowledge, more aggressive treatment is considered mandatory for these tumors ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding after thyroidectomy is a well-known complication, but thanks to improvements in haemostasis, it has become a rare occurrence. However, despite its rarity, if bleeding is not diagnosed early and correctly managed it can become a potentially life-threatening condition [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%